Variational inequalities and the principle of virtual displacements - N. A. Demyankov (Моделирование и анализ информационных систем, 2010)
The existence of a solution of the inclusion 0 ε A(x) + NQ(X) is provexl, in which A is a multivaluexl pseudomonotone operator from the reflexive space V to the conjugate space to it V*, NQ is a normal cone to the weakly compacct and, generally speaking, not convex set Q С V, with nonzero euler characcterization Ӽ(Q).